Where To Sell ? : Market Facilities And Agricultural Marketing - Shilpi, Forhad Jahan (The World Bank, 2008)
This paper analyzes the effect of facilities and infrastructure available at the market place on a farmer's decision to sell at the market using a comprehensive survey of farmers, markets and villages conducted in Tamil Nadu, India in 2005. The econometric estimation shows that the likelihood of sales at the market increases significantly with an improvement in market facilities and a decrease in travel time from the village to the market. The results suggest that wealth reduces a farmer's cost of accessing market facilities more than it increases her/his opportunity cost of leisure. The wealthy farmers are able to capture a disproportionate share of the benefits of facilities available at congested markets. The policy simulation, however, shows that the marginal benefits from an improvement in market facilities will favor poorer farmers in the context of India